Does Private Tuition Facilitate Learning? A Study among Children Enrolled in Government Primary Schools - Dr. Tanmoy Kumar Pal ,; Dr. Subhrangsu Santra , (IJRDO- Journal of Educational Research, 2024)
The phenomenon of shadow education or private tuition has become an important part of students' lives in India. This trend is not limited to secondary education but has also expanded to primary school levels, highlighting its growing demand. The current paper aims to understand the attitude of parents of children enrolled in rural primary schools, and to understand how private tuition influences the level of learning of primary school-going children. The data used in this paper were collected from parents and primary-school-going children living in two (2) districts of West Bengal in India. Standardized learning assessment tools were used to assess the level of English and Arithmetic learning. Jonckheere -Terpstra Test for Ordered Alternatives were conducted to test hypotheses regarding the relation of private tuition and learning levels of students in each subject. Many parents pointed out that private tuition has become unavoidable because schools were 'inadequate'. The reasons cited by parents were rather connected to the socio-economic condition of the households. Based on the results of the statistical tests, it seemed that private tuition improved the English reading abilities of the children to some extent only but failed to improve the Arithmetic ability of the children. Qualitative discussions with children and parents revealed that parents were of the view that their children needed to be kept 'under pressure' and 'regular practice'. Private tutors kept the students under pressure to memorize the letters, words, and texts by repeated practice. The strategy of memorisation was fruitful in recognising letters and words which were indicators of language reading ability, but memorisation was not a good strategy for improving Arithmetical ability. This could be a reason behind not finding any association between private tuition and Arithmetical ability.